Sustainable Primary Education in Andhra Pradesh During COVID-19 - Dake Pranavi; Teki Surayya; Dake Deepika (Universitas Andalas, 2021)
Sustainable development describes the simultaneous maintenance of balance between socio-economic development and environmental sustainability without jeopardizing the future generation's potential to serve their own needs. The main aim of this article is to analyze the sustainability attained by government schools in Andhra Pradesh by providing education to elementary pupils during COVID-19. The unexpected outbreak of the deadly virus COVID-19 wreaked havoc on educational systems, harming children's education. In response to the lockdown, all educational institutions were closed for an extended length of time and remained shuttered even today. According to the information gathered, the government of Andhra Pradesh took all necessary safety measures to ensure the accessibility of government elementary schools and to minimize primary school dropouts. They televised the online lessons to every class at periodic intervals on regional government channels for students. Pupils were given worksheets to exercise according to the curriculum aired on television. These worksheets were submitted for review to the concerned faculty by students' parents. The children were given dry rations monthly as part of the